RESILIENT MODULUS, DYNAMIC MODULUS AND FATIGUE PERFORMANCE OF STONE MATRIX ASPHALT (SMA) WITH ELVALOY MODIFIED ASPHALT BASED ON AASHTO 2008 SPECIFICATION - AS (NIM : 26912310), SEPTIAN
Road pavement technology has been growing rapidly in developed countries. One type of pavement that is rarely found in Indonesia is SMA (Stone Matrix Asphalt). SMA is a gap-graded mixture which has an advantage in retaining cracks and ruts in the pavement. It's expected to be a solution in pavement failures problems in Indonesia. In addition, the use of polymer modified asphalt is expected to improve the characteristics of the bitumen so as to provide good performance on pavement. Elvaloy modified asphalt is used at this research as a comparison against the mixture using conventional asphalt. Mix design carried out by Marshall Method wherein the characteristic properties refers to AASHTO specifications. The performance of the mixture is obtained through mechanistic testing i.e. Marshall Test, Dynamic Modulus, Resilient Modulus and fatigue crack using four-point loading method. Dynamic Modulus test can be used to develop a master curve of each mixture. Based on its characteristics, Elvaloy modified asphalt gives stiffer and less susceptible in case of temperature changes. In general, using Elvaloy modified asphalt mixture indicates better performance, with optimum use of Elvaloy as much as 1%. But using Elvaloy in large numbers will complicate the mixing thereof, are so difficult to achieve peak performance. Overall, the SMA mixture using Elvaloy modified asphalt suitable for use in SMA mixture and can be considered to be an alternative solution to prevent the problems of road damage in Indonesia.